The metalloprotease SepA governs processing of accumulation‐associated protein and shapes intercellular adhesive surface properties in Staphylococcus epidermidis. Issue 5 (26th January 2017) - Paharik, Alexandra E.; Kotasinska, Marta; Both, Anna; Hoang, Tra‐My N.; Büttner, Henning; Roy, Paroma; Fey, Paul D.; Horswill, Alexander R.; Rohde, Holger
Summary: The otherwise harmless skin inhabitant Staphylococcus epidermidis is a major cause of healthcare‐associated medical device infections. The species' selective pathogenic potential depends on its production of surface adherent biofilms. The Cell wall‐anchored protein Aap promotes biofilm formation in S. epidermidis, independently from the polysaccharide intercellular adhesin PIA. Aap requires proteolytic cleavage to act as an intercellular adhesin. Whether and which staphylococcal proteases account for Aap processing is yet unknown. Here, evidence is provided that in PIA‐negative S. epidermidis 1457Δ ica, the metalloprotease SepA is required for Aap‐dependent S. epidermidis biofilm formation in static and dynamic biofilm models. qRT‐PCR and protease activity assays demonstrated that under standard growth conditions, sepA is repressed by the global regulator SarA. Inactivation of sarA increased SepA production, and in turn augmented biofilm formation. Genetic and biochemical analyses demonstrated that SepA‐related induction of biofilm accumulation resulted from enhanced Aap processing. Studies using recombinant proteins demonstrated that SepA is able to cleave the A domain of Aap at residue 335 and between the A and B domains at residue 601. This study identifies the mechanism behind Aap‐mediated biofilm maturation, and also demonstrates a novel role for a secreted staphylococcal protease as a requirement for the development of a biofilm. Abstract : Cell wall‐anchored adhesin Accumulation associated protein (Aap) significantly contributes to biofilm formation. Mature full length Aap prevents cell aggregation. High activity of metalloprotease SepA, such as in the absence of repressor SarA, results in increased cleavage of Aap and subsequent biofilm formation. Processing of Aap is primarily observed within the A domain at residue 335, removing the portion N‐terminal to the lectin‐like domain, but can also involve removal of the entire domain. Cleavage of Aap favours bacterial aggregation and biofilm formation. Thus, protease expression levels modulate adhesive S. epidermidis surface properties, biofilm formation and surface colonization. Biofilm formation is a key virulence mechanism in Staphylococcus epidermidis medical device‐associated infections. Accumulation‐associated protein (Aap) contributes to biofilm formation by mediating bacterial aggregation, but requires proteolytic modification to become functionally active. Here we show that the secreted staphylococcal metalloprotease SepA is required for Aap‐dependent biofilm formation. The global virulence regulator SarA is a strong repressor of SepA production and thus, Aap processing and subsequent biofilm formation. This study identifies the mechanism behind Aap‐mediated biofilm maturation, and demonstrates a novel role for a staphylococcal protease as a requirement for the development of a biofilm.